Strategi Pengembangan Usaha Badan Usaha Milik Gampong (BUMG) Gampong Teungoh Kecamatan Nisam - Ahyar, Juni; Asnawi, Asnawi; Bachri, Naufal; Ikramuddin, Ikramuddin; Rahman, Bobby (Universitas Malikussaleh, 2024)
The BUMG business plan is very important as a basic guide for determining profitable future business activities. Preparing a logical business plan based on market information allows BUMG's goals to be achieved effectively and efficiently. Basically a business plan describes the business activities that will be carried out in the coming period. BUMG Karya Mandiri is 1 of 188 BUMGs in Kutai Kartanegara Regency and is located in Gampong Teugoh, Nisam, North Aceh. BUMG Karya Mandiri was founded in 2016 but started to be active again starting in December 2020 with a second management formed through Gampong deliberations. Since becoming active again, BUMGa Karya Mandiri has run its first business unit, namely buying and selling Tandang Fresh Fruit (TBS) Palm Oil and has only been running for two (2) months. Purchase from farmers in Muara Batu and sell to factories. Based on the information obtained, the BUMG planning and budgeting process has been running but has not been carried out optimally. This is because in practice, BUMG still has 1 business unit and is considering diversifying its business, but everything is still an oral and unwritten contract. Apart from that, other known problems include a lack of capital resources, business premises that are not yet representative, management of income and expenditure plans that have not been designed well, and human resource capabilities that are not yet adequate, and there is no good internal control. Based on the results of the material presentation and discussion, and apart from other problems (business unit limitations), it can be concluded that PKM partners have credibility, competence and meet the qualifications in identifying components and indicators related to BUMG planning and budgeting with existing conditions.